(untitled) (Research, Society and Development, 2021)
Objective: To understand the role of the preceptor nurse in the in-service training process of nursing residents. Methodology: Qualitative, descriptive and exploratory study, in which eleven nurses from a military hospital participated. A semi-structured questionnaire containing questions related to the preceptors’ attributions and perceptions with nursing residents was used for data collection. The data were analyzed and grouped into four thematic categories, being discussed in the light of scholars linked to the theme. Results: It was understood that the preceptor is a mediator of knowledge and professional training of residents, adopts teaching-learning strategies to facilitate the exchange of knowledge and establishes relationships based on mutual respect, trust and autonomy of his students. Conclusion: The health institution needs to encourage the improvement of competences and skills of preceptors in order to achieve excellence in the teaching process, since knowledge is not static and education must accompany scientific innovations and the demands of the labor market and society.